2011
DOI: 10.5210/fm.v16i2.3316
|View full text |Cite
|
Sign up to set email alerts
|

Open data: Empowering the empowered or effective data use for everyone?

Abstract: This paper takes a supportive but critical look at “open data” from the perspective of its possible impact on the poor and marginalized and concludes that there may be cause for concern in the absence of specific measures being taken to ensure that there are supports for ensuring a wide basis of opportunity for “effective data use”. The paper concludes by providing a seven element model for how effective data use can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
224
0
29

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(255 citation statements)
references
References 0 publications
2
224
0
29
Order By: Relevance
“…Second, further studies may be undertaken regarding the quality issues pertaining to OGD to ascertain users' perceptions regarding quality of OGD. Third, the present study remained silent on the "digital divide" (Gurstein, 2011) in India which is indicative of differential OGD use. Since this study covered respondents comprising of well-educated and urban populace, the impact and utility of OGD for rural areas remains to be explored.…”
Section: Limitations Of the Study And Future Research Directionsmentioning
confidence: 80%
“…Second, further studies may be undertaken regarding the quality issues pertaining to OGD to ascertain users' perceptions regarding quality of OGD. Third, the present study remained silent on the "digital divide" (Gurstein, 2011) in India which is indicative of differential OGD use. Since this study covered respondents comprising of well-educated and urban populace, the impact and utility of OGD for rural areas remains to be explored.…”
Section: Limitations Of the Study And Future Research Directionsmentioning
confidence: 80%
“…( [40] For Gurstein, the processes of interpreting data and subsequently being able to make 'effective use' of this same data are just as important as ensuring access to data. He concludes that any critical analysis of open data has to involve questioning how and under what conditions data is contextualized and given meaning ( [27], p. 4). In other words, storytelling with data or providing access to raw data cannot be understood in isolation from how those stories or that access are interpreted and in what way those who interpret the data are able to incorporate it into their lives.…”
Section: Data and The Objectivity Regime's Practicesmentioning
confidence: 99%
“…For the purposes of this paper, we define openness as 'efforts to extend access to "data"' ( [27], p. 1). This definition of openness draws inspiration from Gurstein's critical examination of open data.…”
Section: Openness: Extending Access To Datamentioning
confidence: 99%
“…Gurstein advances the term 'effective use' to delineate between the opportunity to use a technology, and the realization of its transformative potential [6], [7]. He defines it as the capacity to successfully use ICTs (information and communication technologies) to accomplish a particular goal.…”
mentioning
confidence: 99%
“…He defines it as the capacity to successfully use ICTs (information and communication technologies) to accomplish a particular goal. Originally advanced to critique the notion of the 'digital divide,' the gap between highand low-resource people in their access to ICTs [6], Gurstein also found that access to open data was also conflated with its use [7]. The theory of effective use proposes multiple factors that determine or impede use of a technology (or data) aside from users' access to it: (1) internet, (2) technology access, (3) user technology skills, (4) usable formats, (5) user knowledge and sense making, (6) community resources, and (7) formal governance structures that support the intended use.…”
mentioning
confidence: 99%